VALIDITY AND RELIABILITY OF KNOWLEDGE AND HEALTH BELIEF MODEL (HBM) IN PULMONARY TUBERCULOSIS PATIENTS AT KEDUNGMUNDU AND TLOGOSARI WETAN COMMUNITY HEALTH CENTERS IN SEMARANG CITY - Cahyanti, Pipit; Al Farizi, Gilang Rizki; Arini, Yovita Dwi (STIKES Telogorejo Semarang, 2024)
Tuberculosis (TB) is a contagious disease caused by a Mycobacterium tuberculosis infection, also known as acid-fast bacteria. To achieve a cure for TB patients, it is possible to increase knowledge and treatment compliance behavior. The Health Belief Model (HBM) is an effective treatment widely used to improve compliance and health behavior. This study aims to measure the validity and reliability of the knowledge construct and the HBM in pulmonary tuberculosis patients at the Kedungmundu Health Center and Tlogosari Wetan Health Center, Semarang City. This research adopted a quantitative observational design with a cross-sectional approach. The results show that the validity test was based on the corrected item value of 0.361, while the reliability test used internal consistency techniques on the Cronbach Alpha value of 0.70. Meanwhile, the results of the knowledge construct had a validity value of 13 items with a corrected item value of 0.361 and reliability with a Cronbach's alpha value of 0.796. Also, the HBM construct to measure compliance and behavior had a validity value of 20 items with a corrected item of 0.361 and reliability with a Cronbach's alpha of 0.817.